(untitled) (International Journal of Food and Nutritional Sciences, 2024)
Aim: The aim of this study was to validate a method for assessment of mastication in children. Methods: A video-based method is used for the assessment of mastication in children. Assessment parameters include bilateral and cyclic chewing, cutting ability and bolus formation. A sample of 10 children was selected in the age group of 6-12-year-old whose video of carrot chewing was recorded by a parent in a manner explained to them. Two examiners independently assessed the videos for the purpose of validation. Results: The bilateral and cyclic chewing had 100% of level of agreement while cutting ability and bolus formation had 38% and 46% of agreement respectively using kappa statistics. Conclusion: The proposed scale of mastication will require further validation pertaining to video standardization and prior consensus on the working definitions.